Pengaruh Kinerja Perusahaan Terhadap Return Saham - Heikal Muhammad Zakaria (Accounthink, 2018)
This study aimed the influence of Company's performance as measured by the ratio of PER on stock returns. This research method using quantitative methods. Hypothesis using a regression model. The sample uses the best companies according to the OJK in 2013 and took the company's data in the period during 2009-2013. The results of this study provide empirical evidence that the company's performance is proxied by the ratio of PER positive and significant impact on Stock Return. Keyword : Company Performance , PER , Stock Return